Catecholamine secretion during hypoxia in nicotinic receptor-desensitised rainbow trout, Oncorhynchus mykiss. - Lapner, Katherine Nancy. (University of Ottawa (Canada), 2002)
Experiments were performed in vivo using an extra-corporeal blood loop (EC-loop), on chronically cannulated adult rainbow trout ( Oncorhynchus mykiss) to determine whether the ability of fish to respond to acute hypoxia was impaired by an intravenous nicotine infusion (1.3 x 10-5 mol kg-1 h -1; designed to desensitise chromaffin nicotinic receptors). Respiratory and cardiovascular measurements taken throughout the nicotine infusion of the desensitisation protocol indicate that non-chromaffin, neuronal nicotinic receptors also appear to be stimulated and to desensitise. The next set of experiments showed that despite nicotinic receptor desensitisation induced by intravenous infusion of nicotine, plasma catecholamine levels were increased to similar levels (adrenaline plus noradrenaline = 125--200 nmol l-1) as in control fish during severe hypoxia (40--45 mm Hg). (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.